Analise morfológica e molecular de populações de Otocinclus cocama REIS, 2004 (Loricariidae, Siluriformes) na Amazônia Peruana - Mejia de Loayza, Jose Eduardo (2021)
Otocinclus Cocama, Reis, 2004, is placed in the subfamily Hypoptopomatinae originally described from Jenaro Herrera in the Ucayali River, Peru, is distinguish from all its congeners by two autapomorphies: a unique color pattern, consisting of vertically elongated blotches spanning from a dorsal midline to the ventral portion of flanks, and by a complete lateral line. The species is known only from the type locality and is estimated to have a restricted distribution, being assessed as Endangered by the IUCN. However, in the ornamental fish trade, a second morphotype of O. cocama collected in the Tigre River basin is known, with a greater number of vertically elongated blotches spanning along the body. Both morphotypes are known and very popular in the international aquarium fish trade, at least since 2000, and are exported under the name Otocinclus "zebra". The aim of this work was to assess the phylogenetic relationships and significant variations between specimens from different geographic areas, testing the occurrence of divergence and biological speciation between different populations of O. cocama, through the use of geometric morphometry and partial DNA sequences of four mitochondrial genes. 61 specimens deposited in the fish collections of the Natural History Museum of the Universidad Nacional Mayor de San Marcos, Lima, Peru (MHNSM) and the Museum of Science and Technology PUCRS, Porto Alegre (MCP) were analyzed. The geometric morphometric analysis based on 11 homologous landmarks in order to find possible variations in terms of shape and size of the centroid did not allow to identify differences between the populations of the two basins. Phylogenetic analyzes based on the reconstruction of maximum likelihood trees, genetic distance, species delimitation by the GMYC (Generalized Mixed Yule-Coalescence) model, and haplotype network analysis confirmed that O. cocama is formed by a single genetic group with two morphotypes that are well differentiated by the number of elongated blotches throughout the body for each hydrographic basin. These results contribute to future research that aims to evaluate the morphological variation that could occur between different populations of Otocinclus species.